STUDI KOMPARATIF PRESTASI SISWA (Mengikuti dan tidak Mengikuti Ekstrakurikuler ROHIS) - Eka Yanuarti (IAIN PAREPARE, 2016)
A teacher has to be aware that every student he faces is entitled to a good teaching. But in his daily duties the teacher is faced with a challenge of giving the same teaching to different students. We know that humans are endowed with interests and talents, but it becomes wasteful when the interests and talents are not well established and channeled in accordance with the expectation so that less result an achievement. We honestly admit that not all students are able to master the subjects taught in the classroom when in fact that is what should be a provision for them, of course this is caused by many factors, these factors can be interest, study time and disorders when they want to learn. So that their ability to the fields taught in the classroom is not maximal. Every student is entitled to a good education. Schools should therefore provide a special venue for the development of interests, talents, and the addition of students' knowledge in the areas they love so they can hone their interests and talents, and add to their knowledge, such as Rohis extracurricular.